Urbanization-induced site condition changes of peri-urban cultivated land in the black soil region of northeast China. (September 2017) - Li, Wenbo; Wang, Dongyan; Li, Hong; Liu, Shuhan
Graphical abstract: Highlights: A patch-scale site assessment model for cultivated land based on cultivated landscape and location was employed. Spatiotemporal changes in the site conditions of peri-urban cultivated land under the pressure of urbanization was measured. Cultivated land loss was prominent from 2004 to 2014 and urban sprawl rate was found to be accelerating in the study area. Site conditions of peri-urban cultivated land are generally deteriorating, and the urban fringe is a hot spot for the deterioration. Due to site condition deterioration, the actual loss of cultivated land resources will overshadow direct occupation by urbanization. Abstract: The site condition of cultivated land greatly influences the utilization and management of cultivated land resources and is an element that is disturbed tremendously by urbanization. Since the rejuvenation of the northeast old industrial base strategy in 2003, urbanization in northeast China has progressed rapidly. The excessive urban sprawl has profoundly changed land use structure in the peri-urban area of the black soil region, and the subsequent site condition changes will impede the full utilization of cultivated land resources. This study used the suburb of Changchun Kuancheng District as an empirical case, and employed a patch-scale site assessment system to analyze dynamic changes in cultivated land site conditions at a typical rural-urban interface of the black soil region from 2004 to 2014. Cultivated land loss and land use changes were prominent in the study area and the land conversion rate was shown to be accelerating. Most of the occupied cultivated land was converted to urban areas such as industrial land or urban settlements. However, a part of the occupied cultivated land was left unutilized, which indicates how the urban sprawl is jeopardizing benefits of both urban development and cultivated land protection. Besides direct occupation of cultivated land resources, urbanization has led to a loss of cultivated land with good site conditions and a deterioration of the site conditions of unconverted cultivated land in the peri-urban area. Urbanization has fragmented peri-urban cultivated land, increased farming distance and brought more frequent anthropogenic disturbances. On the other hand, it has also improved transportation conditions and the local ecological environment. As site condition is believed to be closely related to both cultivated land loss and cultivation abandonment, the deterioration will aggravate the loss of cultivated land resources in a disguised form.